Development of Test and Measurement Tools Standing Stork Test Android Based - Andika Putranto Hutagalung; Imran Akhmad; M. Irfan (UNIB Press, 2023)
The purpose of this research is to produce a test tool and measurement of standing stork test based on Android. The type of research used in this research is development research with Research & Development (R&D) research design from Borg and Gall. This research was conducted with 9 research stages namely, (1) Research and information collecting, (2) Planning, (3) Develop preliminary form of product, (4) Preminary field testing, (5) Main product revision, (6) Main field testing, (7) Operational product revision, (8) Operational field testing, (9) Final product revision. The population in this study used Sports Science Faculty Students and Aceh-North Sumatra PON Pelatda Athletes. The sampling technique used purposive sampling with Phase I trials of 20 FIK students and Phase II trials of 30 athletes of Pelatda Taekwondo Sumut. Furthermore, from the Phase I trial, totaling 20 people showed a figure of 89% with Very Eligible criteria, then from the Phase II trial, totaling 30 Aceh-North Sumatra PON Pelatda athletes showed a figure of 91% with the Very Eligible category. From the results of the research/feasibility test carried out by test and measurement experts, IT experts and sports academic experts, it shows a score of 96% in the Very Eligible category, so it can be used. On the basis of the data obtained, the development of an Android-based standing stork test and measurement tool was declared feasible to be developed as a test and measurement tool for balance.